3-D P wave velocity structure of Marmara Region using local earthquake tomography - Işık, Sezim Ezgi. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2013., 2013)
The 3D P wave velocity model of upper and lower crust of the Marmara Region between 40.20 - 41.20 N and 26.50 - 30.50 E is obtained by tomographic inversion (Simulps) of 47034 P wave arrivals of local earthquakes recorded at 90 land stations, 30 OBO stations and 14162 shot arrivals recorded at 35 OBO stations (Seismarmara Survey, 2001) between October 2009 and December 2012. We first obtained a 1D minimum model with Velest code in order to use it as an initial model for 3D inversion with 648 well located earthquakes located within the study area. We first developed a 1D model by VELEST code then used it as an initial model for 3D tomography. After trial 3D inversions we decided to create a more adequate initial model for 3D inversion. Choosing the initial model we estimated the 3D P wave velocity model representing the whole region both for land and sea. The results are tested by making Checkerboard Test, Restoring Resolution Test and Characteristic Test, and the reliable areas of the resulting model is defined in terms of RDE, DWS, SF and Hit count distributions. By taking cross sections from the resulting model we observed the vertical velocity change along profiles crossing both land and sea. All the profiles crossing the basins showed that the high velocities of lower crust make extensions towards the basin area which looks like the force that gives a shape to the basins. Under the north of the Central Basin and Çınarcık Basin high velocity zones appeared which look like resisting walls holding the north of the basins between 5 km and 15 km. The same is also observed under the southern Tekirdağ Basin between 5 km and 15 km. These extensions of lower crust towards the basins appeared with an average velocity of 6.3 km/s. These extensions might be the result of the deformation due the shear in the region and it is also interpreted that the development of these high velocities coincides with the development of the basins. Thus, both the basins and the high velocity zones around them might be resulted from the entrance of the NAF into the Marmara Sea when also a shear regime is dominated due to the resistance of the northern Marmara Region (Yılmaz, 2010). The seismicity is observed between 5 km and 15 km after the 3D location of the earthquakes. The locations of the earthquakes improved and the seismogenic zone is determined well, between 5 km and 15 km. The depths of the pre-kinematic basement and crystalline basement showed great differences under the sea. It is observed that the velocity under sea becomes compatible with land after 8 km.
Keywords: Seismic tomography.